Financial Derivatives: Myths and Realities - Ramanjaneyalu, N.; Hosamani, A. P. (Indian Journal of Finance, 2008)
The Indian financial market has undergone paradigm changes in the last two decades. One of the significant changes is the introduction of derivatives in the year 2000. In March 1998, the L. C. Gupta Committee (LCGC) submitted its report recommending the introduction of the derivatives markets. The Committee strongly favours the introduction of financial derivatives in order to provide the facility for hedging in the most cost-efficient way against market risk. Even after seven years, from introduction of derivatives, market participants especially small-retail individual investors are not familiar with the concept of derivatives. Still they have misconceptions about derivatives. They strongly believe in the myths of derivatives. Indeed, they feared derivatives due to lack of knowledge about them and their use. Access to risk-management instruments should not be feared but, should be embraced with caution to help investors manage the circumstances of the market. In this paper, a small attempt is made to demystify the myths of derivatives.